STRATEGI PENGEMBANGAN AGRIBISNIS JAMBU METE DI KECAMATAN BULAGI KABUPATEN BANGGAI KEPULAUAN - Hadyanti Mangopo; Syaiful Darman; Hadayani Hadayani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
The objectives of this research were to analyze strengths, weakness, opportunity and threats faced by cashew agribusiness development; to determine appropriate alternative formulation strategy to develop cashew agribusiness, and to determine prioritized strategy selected for developing cashew agribusiness.  The population of the research was cashew farmers dwelling in Bulagi sub district.  The unit population was purposively determined in Peling Seasa village as it has largest area of cashew plantation as well as largest number of cashew farmers although the plantation productivity is very low.  Respondent samples in this research were 20 people consisting of 18 farmers and 2 field extension officers.  Data were obtained through observations, interviews, and focus group discussion (FGD). The data then was analyzed using SWOT analysis.  The results of the SWOT analysis suggested that the strengths of the cashew agribusiness included (a) agro-ecology, (b) vast land area availability, (c) sufficiently long experience in farming, (d) grow well in marginal land, and (e) sufficient labor availability.  Whereas, opportunity factors were (a) high market demand, (b) forage integration, (c) harvest processing and pseudofruit utilization, (d) government support availability, and (e) increasing pricetrend of dried cashew nut.  The results of SWOT matrix analysis showed that the main strategy implemented is minimizing the weakness factors in order to maximizing the opportunity factors.  Based on the main strategy, activities proposed include: (1) recovering soil fertility through organic fertilizer addition, (2) increasing production through intensification, (3) improving quality and quantity of products through cashew tree rejuvenation and thinning, and (4) enabling the farmers to create various cashew nuts            based products. Keywords: Cashew Nuts, Development Strategy, and Production.